Teachers’ work engagement and burnout profiles: Associations with sense of efficacy and interprofessional collaboration in school - Holmström Anni; Tuominen Heta; Laasanen Miia; Veermans Marjaana (Elsevier, 2025)
This study provides new insights into the work-related well-being of teachers, defined here as engagement and burnout, by investigating their associations with the teachers’ sense of efficacy and interprofessional collaboration in school. Using a person-oriented approach and latent profile analysis, a sample of Finnish comprehensive school teachers (N = 355) were classified based on their work engagement and burnout. Three profiles were identified: engaged, engaged-exhausted, and burned-out. Teachers with distinct profiles differed from each other in terms of their sense of efficacy and experiences of interprofessional collaboration, suggesting that both might have an important role in enhancing work engagement and preventing burnout.